Morphological and molecular characterization of some NERICA mutant lines under drought condition - Hasan, MN; Bhuiyan, MJH; Begum, SN; Raffi, SA; Razia, S (Progressive Agriculture, 2015)
To ensure the productivity of rice in drought condition, NERICA varieties of African origin has been introduced in Bangladesh and subsequently mutant lines are also developed for improving the performance further. The present study was undertaken to screen out better drought tolerant mutant lines of NERICA having other desirable traits. Thirteen NARICA mutant lines, four susceptible (BINA dhan8, BINA dhan10, BINA dhan11 and BINA dhan12) and one tolerant (BRRI dhan56) varieties were included in the experiment and selection was based on morphological and molecular characteristics. The plants were grown in pot containing 9 kg of soil and when they were 60 days old, drought was imposed by adding 1L of distilled water at every four days interval till harvesting. The quantity of water applied to control pots was double. The results showed that important yield contributing morphological attributes like days of 50% flowering, plant height, total number of tiller hill-1, panicle length, 100 seed weight, fresh weight of plant and dry weight of plant were significantly positively regulated due to drought in N10/300/P-2(1)-3-5, N1/250/P-6-2-7 and N10/300/P-2(1)-6-13 mutant lines. The findings of genetic diversity analysis through SSR markers RM32, RM202, RM351 and RM510 for N10/300/P-2(1)-3-5, N1/350/P-2-2-6 and N1/250/P-6-2-7 lines appeared to resemble to that of control (BRRI dhan56) from the UPGMA dendrogram. Based on morphological, molecular characteristics and UPGMA dendrogram study, mutant lines N10/300/P-2(1)-3-5 and N1/250/P-6-2-7 lines appeared superior as genetic material for developing better drought tolerant rice varieties. Progressive Agriculture 26:15-21, 2015